PENGARUH MODEL TEAM GAMES TOURNAMENT BERBANTUAN MEDIA ULAR TANGGA ECOLAND TERHADAP PEMAHAMAN KONSEP KESEIMBANGAN EKOSISTEM SISWA KELAS V SEKOLAH DASAR - Elvina Salsabila Putri; Feni Kurnia; Yorenza Meifinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to determine the effect of the Team Games Tournament (TGT) model combined with the Ecoland snakes-and-ladders game on the conceptual understanding of fifth-grade elementary school students. This study employed a quantitative, pre-experimental approach using a one-group pretest-posttest design. The study involved 20 fifth-grade students. Data were collected using a written test consisting of five essay questions. The data analysis began with a normality test, which revealed that the data were not normally distributed (Sig < 0.05). Consequently, hypothesis testing was shifted to the non-parametric Wilcoxon Signed Rank Test. The test results showed an Asymp. Sig. value of 0.000 < 0.05. The conclusion of this study states that the integration of the TGT model with the Ecoland educational media has an effect on elementary school students’ understanding of the concept of ecosystem balance.